Whipping as punishment from civil and Shariah perspectives with reference to its practice in Malaysia - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia Sdn. Bhd., 2018)
The severity or gravity of whipping punishment from the civil and Shariah perspective is discussed in this article with reference to its practice in Malaysia. Appropriate punishment to be meted-out on the offender must befit the crime committed so that the courts take heed of the public abhorrence of such crimes.